STORYTELLING: ENHANCING VOCABULARIES FOR CEREBRAL PALSY STUDENTS - Raita Gina Aprilina (Journal of English and Education, 2015)
This paper reported on a study concerned with teaching vocabulary using storytelling technique in one of SLBs in Bandung. This study aimed to find out the cerebral palsy students’ ability in English vocabulary before and after the treatment, and to find out whether storytelling significantly improved English vocabulary of students with cerebral palsy. This study used an experimental method with single subject research with A-B-A design which involved two participants. This study revealed that the storytelling technique increased the students’ score in general, but six sessions of treatments still could not yet give significant improvement to the cerebral palsy students’ ability in English vocabulary.